Vegetation History of Karacabey Longoz Forest and Surrounding Area During the Last 250 Years (Bursa, Türkiye) - Nurgül Karlıoğlu Kılıç; Rüya Yılmaz Dağdeviren; Dilek Aykır; Şakir Fural; Serkan Kükrer; Turhan Doğan; Yunus Emre Mutlu; Nurettin Yakupoğlu (Coğrafya Dergisi)
In this study, a 24-cm-long sediment core was taken from Poyraz Lagoon located on the northern side of Karacabey district in Bursa, northwest of Türkiye, using KAJAK gravity core sampling. The bottom sediment was dated using one AMS radiocarbon date on bulk organic carbon. The 13δ corrected radiocarbon age was determined as 238±24 BP. Sediment sub-samples were taken at 4-cm intervals along this core, and pollen slides were prepared using the standard method. A total of 250 terrestrial pollen grains were counted in each sediment sample. The aim of this study was to determine the vegetation history of Karacabey Longoz (Floodplain) Forest and its surrounding area, which have diverse habitat mosaics, over the last 250 years. Palynological evidence indicates that the vegetation around this lagoon basin was dominated by Fraxinus, Alnus, Carpinus, Quercus (deciduous oaks), and Corylus. The increase in the pollen percentage of Fraxinus, Alnus, and Ulmus, which are characteristic species of Longoz forests, particularly in the KRC-2 zone, indicates that the presence of these taxa in the area has increased from 1850 AD to the present. Additionally, the increased pollen percentage of anthropogenic indicator species such as Castanea, Olea, Chenopodiaceae, and Poaceae in the upper zone of the pollen diagram indicates that the Longoz vegetation in this region has undergone changes due to human impact since 1850 AD.